Blockchain-based FinTech and ESG Compliance in Energy Supply Chains: The Moderating Role of Supply Chain Governance - AlMaaitah, Nebal (International Journal of Energy Economics and Policy, 2026)
This investigation aims at analyzing the interaction between the development of financial technology (FinTech) based on the principle of blockchain and compliance with environmental, social and governance (ESG) criteria in the world of energy supply chains, with a special focus on the moderating role played by supply-chain governance. In view of the escalating regulatory and increasing stakeholder pressures and robustness of sustainability risks plaguing the energy supply chains, digital technologies-a form of blockchain-based FinTech solutions-are increasingly being taken into consideration as tools that can create enhanced transparency, traceability and accountability. A quantitative, cross sectional research design was adopted, and data were gathered using surveys to be distributed to firms involved in energy supply chain and fuel distribution networks operating within the Jordan. The proposed model was evaluated using Partial Least Squares Structural Equation Modelling (PLS-Sem) both for Direct and moderating effects. Empirical findings show that the adoption of FinTech via blockchain has a significant positive impact on ESG compliance in the energy supply chains, which hints blockchain-enabled transparency, smart contracts, and financial integrating platforms have a substantive role in supporting ESG compliance. However, the moderating role of supply chain governance was not supported, suggesting that blockchain-based FinTech may act as a governance-neutral or governance-substituting, built mechanism by putting monitoring and enforcement features directly into digital infrastructures. The study makes a contribution to the literature by presenting empirical evidence from an emerging market setting as well as by challenging common assumptions about the conditional role of governance in digital sustainability initiatives. Practically, the findings provide policy-relevant information to regulators and decision-makers in the energy sector who might want to harness digital finance solutions to drive their ESG compliance policy.